Hypoxaemia during tracheal intubation in patients with hypertensive disorders of pregnancy: analysis of data from an obstetric airway management registry. (February 2021) - Smit, M.I.; du Toit, L.; Dyer, R.A.; van Dyk, D.; Reed, A.R.; Lombard, C.J.; Hofmeyr, R.
Highlights: Study of peri-induction hypoxaemia and hypertensive disorders of pregnancy. In the anaesthesia peri-induction period, 12% of patients had an SpO2 nadir <90%. Hypertensive patients were twice as likely to become hypoxaemic (19% vs 9%). Increasing body mass index compounded the effect of hypertension on hypoxaemia. Abstract: Background: In South Africa, hypertensive disorders of pregnancy are the leading cause of maternal mortality. More than 50% of anaesthesia-related maternal deaths are attributed to complications of airway management. We compared the prevalence and risk factors for hypoxaemia during induction of general anaesthesia in parturients with and without hypertensive disorders of pregnancy. We hypothesised that hypertensive disorders of pregnancy are associated with desaturation during tracheal intubation. Methods: Data from 402 cases in a multicentre obstetric airway management registry were analysed. The prevalence of peri-induction hypoxaemia (SpO2 <90%) was compared in patients with and without hypertensive disorders of pregnancy. Quantile regression of SpO2 nadir was performed to identify confounding variables associated with, and mediators of, hypoxaemia. Results: In the cohort of 402 cases, hypoxaemia occurred in 19% with and 9% without hypertension (estimated risk difference, 10%; 95% CI 2% to 17%; P =0.005). Quantile regression demonstrated a lower SpO2 nadir associated with hypertensive disorders of pregnancy as body mass index increased. Room-air oxygen saturation, Mallampati grade, and number of intubation attempts were associated with the relationship. Conclusions: Clinically significant oxygen desaturation during airway management occurred twice as often in patients with hypertensive disorders of pregnancy, compounded by increasing body mass index. Intermediary factors in the pathway from hypertension to hypoxaemia were also identified.